2004
DOI: 10.1182/blood-2004-01-0100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lethal irradiation in zebrafish and rescue by hematopoietic cell transplantation

Abstract: The study of hematopoiesis has been greatly facilitated by transplantation of blood cell populations into recipient animals. Efficient engraftment of donor cells generally requires ablation of the host hematopoietic system. The zebrafish has recently emerged as a developmental and genetic system to study hematopoiesis. To enable the study of hematopoietic stem cell ( IntroductionThe study of the biologic effects of ␥ irradiation began over a century ago, 1 but it was not until deployment of the atomic bomb in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 28 publications
7
147
1
1
Order By: Relevance
“…Transplantation of thymocytes and kidney marrow cells from lck:GFP animals resulted in the transient and permanent repopulation of the thymus in the recipients, respectively. These results indicate that the thymus contains only short-term thymic repopulating progenitors, whereas long-term repopulating HSCs are present in the kidney (Langenau et al, 2004).…”
Section: The Use Of Irradiated Recipients For Transplantation Assaysmentioning
confidence: 79%
See 1 more Smart Citation
“…Transplantation of thymocytes and kidney marrow cells from lck:GFP animals resulted in the transient and permanent repopulation of the thymus in the recipients, respectively. These results indicate that the thymus contains only short-term thymic repopulating progenitors, whereas long-term repopulating HSCs are present in the kidney (Langenau et al, 2004).…”
Section: The Use Of Irradiated Recipients For Transplantation Assaysmentioning
confidence: 79%
“…Transplantation of kidney hematopoietic cells from normal donors rescued the 40 Gy-irradiated recipients (Traver et al, 2004). Thus, transplantation of hematopoietic cells from the teleost kidney recapitulates the radioprotective effect of comparable transplants in the mouse model (Lorenz et al, 1951).…”
Section: The Use Of Irradiated Recipients For Transplantation Assaysmentioning
confidence: 94%
“…In addition to many transplantation experiments from embryo to embryo, we also transplanted AGM CD41 + cells into conditioned adult recipients. Whereas we routinely achieve LTR using adult kidney cells transplanted into sublethally irradiated adult hosts (Traver et al, 2004), we have not observed LTR when using any cell population from embryonic donors. In the mouse, it has been demonstrated that embryonic cells do not express class I MHC molecules before E10.5 (Ozato et al, 1985).…”
Section: Research Articlementioning
confidence: 80%
“…Animals were scored for tumors at 25 days of life, killed and fixed in 4% PFA. Subsequently, animals were sectioned and stained by TUNEL or hematoxylin/eosin as described previously (Traver et al, 2004). Tumor sections were photographed under  1000 oil emersion and apoptotic cell number and total cell number were counted per field (n ¼ 3 fields per sample, Supplementary Figure 3).…”
mentioning
confidence: 99%